Profitability Analysis on Company Value with Good Corporate Governance As A Moderating Variable - Florentina Yuniar Pramesti; Maria Rio Rita (International Journal of Social Science and Business, 2021)
Financial performance is a measure of the poor performance of a company. The financial performance is influenced by the business strategy implemented by the company itself. This study aims to analyze the profitability variable on firm value with Good Corporate Governance (GCG) as moderate. The profitability variable was measured using the Return on Assets (ROA) value. Meanwhile, Company Value is measured by Tobin's Q. GCG as a variable is measured by two proxies, the Independent Board of Commissioners and the Audit Committee. The sample in this study was 10 State-Owned Enterprises (BUMN) in finance and insurance listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The technique used in this research is purposive sampling. The study results indicate that profitability has a significant effect on firm value. Based on the value of t count (3.955) > t table (0.677) and the value of Sig (0.000) <0.05. GCG (Good Corporate Governance) can moderate the effect of profitability on firm value based on the value of t count (8.096) > ttable (0.677), and the Audit Committee based on the value of t count (8.332) > ttable (0.677). Profitability can explain the variation of the firm value variable based on the R2 value of 28.5%, and GCG (Independent Board of Commissioners and Audit Committee) can strengthen the relationship between profitability and firm value to 47.7%.